GAMBARAN PEWARNAAN GIGI (STAIN) PADA MASYARAKAT PEROKOK DI RT.12 PERUM GRAMAPURI TAMANSARI KAB. BEKASI - Sabela Ayu Parasati; Yenni Hendriani Praptiwi; Irwan Supriyanto; Isa Insanuddin (Poltekkes Kemenkes Bandung, 2022)
Dental stains are colors that stick to the surface of the teeth, usually due to the color of food, drink, or nicotine content, especially the substance that produces dental stains. Smoking habits can cause stains (stains on teeth), where cigarette smoke containing various substances sticks to the tooth surface which over time will make the tooth surface feel rough. The purpose of the study was to determine the description of tooth staining (stain) in the smokers community in RT 12 Perum Gramapuri Tamansari Kab. Bekasi. This type of research is descriptive research. This research method is a cross sectional study which was conducted in May-June 2022 on 40 people in RT.12 Perum Gramapuri Bekasi Regency. The habit of consuming cigarettes was obtained through interviews using a questionnaire, while stains on teeth were measured through observation. The data is processed and presented in the form of a frequency distribution table. The results of the study found that the most frequent smoking frequency was moderate category smokers with the number of cigarettes smoked 11-20 cigarettes per day. Based on the frequency of smoking, the formation of stains on the teeth is most common in smokers with the moderate category.